2000
DOI: 10.1063/1.1288267
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of the CNN free radical

Abstract: The spectroscopy and photodissociation dynamics of the à 3 ⌸ and B 3 ⌺ Ϫ states of the CNN radical have been investigated by fast beam photofragment translational spectroscopy. Vibronic transitions located more than 1000 cm Ϫ1 above the à 3 ⌸←X 3 ⌺ Ϫ origin were found to predissociate. Photofragment yield spectra for the B 3 ⌺ Ϫ ←X 3 ⌺ Ϫ band between 40 800 and 45 460 cm Ϫ1 display resolved vibrational progressions with peak spacing of Ϸ1000 cm Ϫ1 corresponding to symmetric stretch 1 0 n and combination band 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
5
20
0
Order By: Relevance
“…The value of D 0 obtained in this way is 1.139± 0.019 eV. Together with the heat of formation of CH, 6.149± 0.013 eV, 36,47 this yields a heat of formation, ⌬ f H 0 ͑HCNN͒ = 5.010± 0.023 eV, in agreement with the value of 5.02± 0.18 eV previously reported, 25 but with much less uncertainty. The values of E T max for channel ͑3͒ products ͑CH͑X 2 ⌸͒ +N 2 ͑X 1 ⌺ g + ͒͒ calculated from this value of D 0 are shown as dashed, vertical lines in Fig.…”
Section: A Heat Of Formation Of Hcnnsupporting
confidence: 78%
See 2 more Smart Citations
“…The value of D 0 obtained in this way is 1.139± 0.019 eV. Together with the heat of formation of CH, 6.149± 0.013 eV, 36,47 this yields a heat of formation, ⌬ f H 0 ͑HCNN͒ = 5.010± 0.023 eV, in agreement with the value of 5.02± 0.18 eV previously reported, 25 but with much less uncertainty. The values of E T max for channel ͑3͒ products ͑CH͑X 2 ⌸͒ +N 2 ͑X 1 ⌺ g + ͒͒ calculated from this value of D 0 are shown as dashed, vertical lines in Fig.…”
Section: A Heat Of Formation Of Hcnnsupporting
confidence: 78%
“…25 10,16 There is, however, an exit barrier of about 1.46 eV for dissociation of HCNN ͑X 2 AЉ͒ to HCN ͑X 1 ⌺ + ͒ +N ͑ 4 S͒ products, a process which, in addition, requires intersystem crossing. 16 The results of the present study reveal photofragmentation of HCNN following excitation at energies above 25 600 cm −1 , a range in which no previous spectroscopic studies have been performed on this radical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mass resolution of these experiments hinders the separation of the two mass channels, in previous studies of NCN and CNN we observed the presence of a N 2 ϩC mass channel that was energetically overlapped with a CNϩN mass channel. 38,39 A broadening and shifting of the peaks in the mass spectrum from those of a single channel marked the presence of both channels. A similar trend was not observed in the mass spectrum of the products of NCO photodissociation, indicating that the contribution from the OϩCN mass channel is not substantially greater than the contribution from the NϩCO mass channel in the region of E T р0.71 eV.…”
Section: B Translational Energy Distributions At 193 Nmmentioning
confidence: 99%
“…7,8 The presence of NCN in that reactive environment was confirmed by the observation of a complicated system of bands near 3290 Å. 14 For instance, it has been appointed as an intermediate in the reaction of CH radicals with N 2 , CH͑X 2 ⌸͒ + N 2 ͑X 2 ⌺ g + ͒ → HCN͑X 1 ⌺ + ͒ + N͑ 4 S͒, providing a low energy path to nitrogen atom formation. 10 In addition, ultraviolet emission studies 11 have suggested that the NCN radical is present in the Comet Brorosen-Metcalf.…”
Section: Introductionmentioning
confidence: 94%